Glycomaterials for probing host–pathogen interactions and the immune response - Huang, Mia L (Exp Biol Med (Maywood), 2016)
The initial engagement of host cells by pathogens is often mediated by glycan structures presented on the cell surface. Various components of the glycocalyx can be targeted by pathogens for adhesion to facilitate infection. Glycans also play integral roles in the modulation of the host immune response to infection. Therefore, understanding the parameters that define glycan interactions with both pathogens and the various components of the host immune system can aid in the development of strategies to prevent, interrupt, or manage infection. Glycomaterials provide a unique and powerful tool with which to interrogate the compositional and functional complexity of the glycocalyx. The objective of this review is to highlight some key contributions from this area of research in deciphering the mechanisms of pathogenesis and the associated host response.